23-2v=7(v+1)-v

Simple and best practice solution for 23-2v=7(v+1)-v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23-2v=7(v+1)-v equation:



23-2v=7(v+1)-v
We move all terms to the left:
23-2v-(7(v+1)-v)=0
We calculate terms in parentheses: -(7(v+1)-v), so:
7(v+1)-v
We add all the numbers together, and all the variables
-1v+7(v+1)
We multiply parentheses
-1v+7v+7
We add all the numbers together, and all the variables
6v+7
Back to the equation:
-(6v+7)
We get rid of parentheses
-2v-6v-7+23=0
We add all the numbers together, and all the variables
-8v+16=0
We move all terms containing v to the left, all other terms to the right
-8v=-16
v=-16/-8
v=+2

See similar equations:

| 13x-24=212 | | 3x-10+4x=2(x-4)+9x | | -5-3x+8=30 | | 3x-10=5x+40 | | 5x+8x+9-36=0 | | +4x=+40 | | r/4− 4=1 | | m/4+36=41 | | 47−0u=25 | | B=3.5h=6 | | 47−u=25 | | j+40=-10+7 | | r/9+75=79 | | -122+7j=-8j-2 | | 17-4h=59 | | 59=4h−17 | | 2x-8/x=6 | | 3=×-y | | 27=46+2x-4 | | w/9=72 | | 13x-9x=-12 | | 3*x=1/729 | | f-45=30 | | 1/5×2^x=3.2 | | (2x)^x=12^12 | | -x^2+74x-1200=0 | | 7x+80=122 | | (x+8)^2-30=44 | | 4x2+4x+1=25 | | 12=-28+10c | | 6*a=48a= | | 20-e=12 |

Equations solver categories